Evaluation of the project Pilsen – European capital of culture 2015 - Ježek, Jiří (Journal for Geography, 2016)
The paper deals with the evaluation of the project Pilsen – European Capital of Culture 2015. It is based on a few empiric research studies that were implemented after the project was finished. It presents the city of Pilsen and the project of the European Capital of Culture form its initiation to implementation. It deals with the benefits of the project from the point of view of attendance, investment, tourism, and impacts on the economic development. It also brings the evaluation of the project Pilsen - European Capital of Culture 2015 as seen by the city´s residents.
Keywords: European Capital of Culture; Pilsen; evaluation research